Meliaceae (Sapindales): species richness and distribution in Tabasco, Mexico - Burelo Ramos, Carlos Manuel; Córdova Córdova, Doris; Campos Díaz, Manuel Jesús; Morales-Rodríguez, Neil Ebeth Meled; Álvarez-Jiménez, William; Muñiz-Chavarría, Nahúm; Beauregard Solís, Graciela (Instituto de Ecología, A.C., 2020)
Background and Aims: In order to update the checklist of Meliaceae that occur in the state of Tabasco under the current classification system, a taxonomic review of the family was conducted, contributing to the “Flora de Tabasco” project.Methods: A revision of specimens belonging to Meliaceae was performed in both state and national herbaria. Field work was carried out between 2015 and 2017 sampling a wide array of of natural and secondary vegetation types in Tabasco. The collected material was identified with the use of taxonomic keys and compared with reliably identified herbarium material. Type specimens available in JSTOR Global Plants were also consulted. We provide an identification key for the species of the family in Tabasco. We also performed an analysis of the distribution of the species based on vegetation type and ecological data. Finally, we provide a list of common names and images of several species.Key results: The Meliaceae are represented by 11 species and four native genera; there are also two alien genera (each represented by a single species). Two species constitute new records for the flora of Tabasco. Trichilia is represented by seven species, whereas Guarea has two. The municipalities with the highest number of species are Centro and Teapa with eight species each and Balancán with seven species. Conclusions: The Meliaceae species reported for the study area represent 45.83% of the 24 native species of this family known in Mexico. They are mostly distributed in areas of secondary vegetation and remnants of tropical rain forest close to the borders with Chiapas and Guatemala.